Students’ Grammatical Problems in Writing Simple Paragraphs: Lack of Grammatical Competency or Language Carelessness? - Lely Refnita (Universitas Negeri Padang, 2014)
The real language condition in Indonesia is that most learners of English as a foreign language (EFL) have already had and communicated in their own mother tongues and bahasa Indonesia as the national language. For many reasons, the grammar instruction of EFL is essential to build grammatical competency, language awareness, and communicative ability. Therefore, the instructional processes of English grammar have an important role in order to provide the learners with sufficient grammatical competency and language awareness on English. The grammatical problems made by the students in written communication are not relatively allowed, then. The students’ grammatical problems in writing should be initially corrected and academically improved. This paper, developed based on a part of research results conducted in 2013/2014 academic year at the English Department of FKIP Universitas Bung Hatta, Padang, discusses the forms and types of students’ grammatical problems in writing simple paragraphs. In addition, the discussion continues to analyze whether the grammatical problems found in the learners’ simple paragraphs can be academically assigned as lack of grammatical competency and/or their own language carelessness. The data are students’ grammatical problems found in their written simple paragraphs. The data analysis may reasonably come to the conclusion that most of the grammatical problems belong to student’s lack of grammatical competency and the others to their language carelessness.